Historical Role of the International Communist Movement during the World Anti-fascist War. (2nd July 2016) - An, Jiang
Abstract : The relationship between the international Communist movement and the world anti- fascist war constitutes a major historical theme of our times. As a positive force for democracy and peace, the international Communist movement became a solid political cornerstone of the anti-fascist war. Its enormous sacrifices and contributions made it one of the final forces terminating the fascist political order, and its humanity provided mankind with a just direction in the struggle against war terrorism and for peace idealism. It thus became a major force in effectively advancing the development of democracy and peace. Based on the logic of condemnation, the critical reflections upon fascism made by the Communist movement have provided a value dimension for the building of today's international security system. Based on the logic of construction, the international peace ethics followed by the international Communist movement offer an ideological foundation for the building of the new international order. And based on the logic of development, the new paradigm of world civilization pursued by the international Communist movement has become a political exemplar for the current pursuit of international peace. The political force of the Communist Party of China (CPC), as China's political backbone and advance guard, cannot be overlooked: it influenced the anti-fascist war, the postwar international Communist movement and the democratization of world order. Of course, both the Soviet Union and the Comintern also offered many historical lessons during the anti-fascist war, lessons that merit profound reflection and consideration.